2005
DOI: 10.2174/1573395054065106
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Response Research - SARS Coronavirus Vaccines and Application of Processes to Other Emerging Infectious Diseases

Abstract: The near pandemic caused by the severe acute respiratory syndrome (SARS) emphasized that new and emerging infectious diseases not only continue to plague the world but also how the scientific community can unite to rapidly identify the causative agent and develop strategies such as vaccines to control its spread. The availability of the SARS coronavirus (SARS-CoV) genome sequence paved the way for the identification of recombinant vaccine candidates for SARS. Based on previous successful animal CoV vaccines, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 111 publications
(223 reference statements)
0
12
0
Order By: Relevance
“…The quest for a SARS vaccine manifested itself intensively after the outbreak. During the past years, several strategies against SARS were suggested as vaccines against SARS, including inactivated SARS-CoV, viral vectors such as adenovirus, vaccinia or rhabdovirus, recombinant SARS-CoV proteins, and DNA-based vaccines (reviewed by See et al [39]). The surface glycoprotein S was employed as a primary target for prophylactic vaccine candidates to induce virus neutralising antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The quest for a SARS vaccine manifested itself intensively after the outbreak. During the past years, several strategies against SARS were suggested as vaccines against SARS, including inactivated SARS-CoV, viral vectors such as adenovirus, vaccinia or rhabdovirus, recombinant SARS-CoV proteins, and DNA-based vaccines (reviewed by See et al [39]). The surface glycoprotein S was employed as a primary target for prophylactic vaccine candidates to induce virus neutralising antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies may be considered for vaccination against SARS-CoV, including a whole killed virus (WKV) vaccine, a live attenuated SARS-CoV vaccine, a viral vector such as adenovirus (Ad) or vaccinia virus expressing SARS-CoV genes, recombinant SARS-CoV proteins or DNA vaccines (See et al, 2005). Live attenuated CoVs, killed CoVs, DNA vaccines and viral-vectored vaccines have all been used to successfully vaccinate against animal CoVs (Cavanagh, 2003;Holmes, 2003;Navas-Martin & Weiss, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Live attenuated CoVs, killed CoVs, DNA vaccines and viral-vectored vaccines have all been used to successfully vaccinate against animal CoVs (Cavanagh, 2003;Holmes, 2003;Navas-Martin & Weiss, 2004). Spike (S) protein has been shown to be involved in CoV pathogenesis and several groups have developed SARS vaccines based on the SARS-CoV S protein as a target (See et al, 2005). A DNA-based vaccine (Yang et al, 2004), a modified Ankara vaccinia virus (Bisht et al, 2004) and a recombinant attenuated parainfluenza virus have been shown to induce neutralizing antibodies and reduce pulmonary SARS-CoV replication.…”
Section: Introductionmentioning
confidence: 99%
“…Several potential strategies can be considered for vaccination against SARS-CoV, including a whole killed virus (WKV) vaccine, a live-attenuated SARS-CoV vaccine, a viral vector such as adenovirus or Vaccinia virus expressing SARS-CoV genes, recombinant SARS-CoV proteins and DNA-based vaccines (reviewed by See et al, 2005). In this report, two SARS vaccine approaches were developed in parallel and evaluated for their efficacy in a murine SARS model by the SARS Accelerated Vaccine Initiative described elsewhere (Finlay et al, 2004).…”
Section: Introductionmentioning
confidence: 99%